Long-term outcomes of an esophagus-preserving chemoradiotherapy strategy for patients with endoscopically unresectable stage I thoracic esophageal squamous cell carcinoma. (September 2021) - Suwa, Tatsuya; Ishida, Yuichi; Negoro, Yoshiharu; Kusumi, Fusako; Kadokawa, Yoshio; Aizawa, Rihito; Nakajima, Toshifumi; Okamoto, Yoshiaki; Okuno, Yoshishige; Yamada, Kazunari; Ogura, Masakazu; Murakami, Masao; et al.
Highlights: Endoscopically unresectable stage I esophageal cancer is usually treated by surgery. Operable stage I esophageal carcinomas were treated with our multimodal approach. Based on interim appraisal, most patients were treated with chemoradiotherapy. Although local recurrences were common, half of them were rescued without surgery. We observed favorable long-term survival and esophagus preservation rates. Abstract: Background and purpose: To assess the long-term outcomes of a multimodal approach for maximum esophagus preservation in operable patients with endoscopically unresectable stage I thoracic esophageal squamous cell carcinoma (ESCC). Materials and methods: The medical records of patients with stage I thoracic ESCC treated with our protocol between 1992 and 2005 were retrospectively reviewed. Our protocol consisted of neoadjuvant concurrent chemoradiotherapy, followed by either additional definitive chemoradiotherapy for good responders (CRT group) or surgery for moderate or poor responders (CRT-S group) after an interim appraisal. Results: A total of 51 patients were analysed. The median age of the patients was 67 years. The median follow-up period was 124.8 months. After the interim assessment, 49 and 2 cases were assigned to the CRT and CRT-S groups, respectively. In the intent-to-treat analyses, overall survival (OS), disease-free survival (DFS), cumulative incidence for death from esophageal cancer, and that for loss of esophageal function were 78.9%, 53.5%, 10.5%, and 20.4% at 5 years, and 55.2%, 27.8%, 18.2%, and 22.9% at 10 years, respectively. Grade 3 late toxicities occurred with the following incidences: esophageal stenosis in 1 case, esophageal ulcer in 1 case, and pericardial effusion in 2 cases. No grade 4 or higher toxicities were observed. Conclusion: Long-term survival and esophagus preservation outcomes were favorable, with acceptable toxicities. Our results suggest that CCRT is an alternative treatment for majority of operable patients with endoscopically unresectable stage I thoracic ESCC in combination with salvage therapy.